Developing a school quality ecosystem in Tapin Regency: A best practice of accreditation enhancement by the principal of SMP IT An-Nur - Muhammad Fitriadi; Tri Kardina; Dewi Ayu Ratna Adi Juwita (HAFECS PRESS, 2026)
School accreditation is a strategic instrument in the education quality assurance system that not only serves as an evaluation of the suitability of educational units, but also as a driver for continuous quality improvement. However, high accreditation achievements do not always reflect the formation of an integrated school quality ecosystem, especially in regions that still face challenges in equalizing education quality. This study aims to describe and analyze good practices in strengthening accreditation through the development of a school quality ecosystem at SMP IT An-Nur in Tapin Regency. The study used a descriptive qualitative approach with data collection techniques in the form of document review, observation, and interviews. Data were analyzed through the stages of data reduction, data presentation, and conclusion drawing, and validated through triangulation of sources and techniques. The results show that SMP IT An-Nur's success in achieving A accreditation is supported by integrated data-based school governance, consistent implementation of the Internal Quality Assurance System, contextual learning innovation, a collaborative work culture, and academic supervision oriented towards teacher professional development. These findings indicate that superior accreditation is the output of a quality ecosystem that is built systematically and sustainably, not simply the result of fulfilling administrative documents. The novelty of this research lies in the introduction of the school quality ecosystem concept as an integrative framework connecting school leadership, quality culture, internal quality assurance, and learning practices to support educational quality improvement. This model has the potential to serve as a reference for schools and education stakeholders in strengthening the quality and equity of education at the regional level. Abstrak. Akreditasi sekolah merupakan instrumen strategis dalam sistem penjaminan mutu pendidikan yang tidak hanya berfungsi sebagai evaluasi kelayakan satuan pendidikan, tetapi juga sebagai pendorong peningkatan mutu secara berkelanjutan. Namun, capaian akreditasi yang tinggi belum selalu mencerminkan terbentuknya ekosistem mutu sekolah yang terintegrasi, khususnya pada daerah yang masih menghadapi tantangan pemerataan mutu pendidikan. Penelitian ini bertujuan untuk mendeskripsikan dan menganalisis praktik baik penguatan akreditasi melalui pembangunan ekosistem mutu sekolah di SMP IT An-Nur Kabupaten Tapin. Penelitian menggunakan pendekatan kualitatif deskriptif dengan teknik pengumpulan data berupa telaah dokumen, observasi, dan wawancara. Data dianalisis melalui tahapan reduksi data, penyajian data, dan penarikan kesimpulan, serta divalidasi melalui triangulasi sumber dan teknik. Hasil penelitian menunjukkan bahwa keberhasilan SMP IT An-Nur dalam meraih akreditasi A didukung oleh keterpaduan tata kelola sekolah berbasis data, implementasi Sistem Penjaminan Mutu Internal yang konsisten, inovasi pembelajaran kontekstual, budaya kerja kolaboratif, dan supervisi akademik yang berorientasi pada pembinaan profesional guru. Temuan ini menunjukkan bahwa akreditasi unggul merupakan luaran dari ekosistem mutu yang dibangun secara sistematis dan berkelanjutan, bukan sekadar hasil pemenuhan dokumen administratif. Kebaruan penelitian terletak pada pengenalan konsep school quality ecosystem sebagai kerangka integratif yang menghubungkan kepemimpinan sekolah, budaya mutu, penjaminan mutu internal, dan praktik pembelajaran dalam mendukung peningkatan mutu pendidikan. Model ini berpotensi menjadi rujukan bagi sekolah dan pemangku kepentingan pendidikan dalam memperkuat mutu dan pemerataan pendidikan di tingkat daerah.